Design And Development Of Android Application For Daily Construction Labor Mandor’s With HCD (Human Centered Design) Approach - Abdullah, Ahmad; Muhammad, Meizano Ardhi; Pratama, Mahendra; Septama, Hery Dian (Journal of Applied Science, Engineering and Technology, 2023)
The construction industry is a development sector in Indonesia with a constantly increasing number of projects annually. In the projects, there is usually a construction manager (or 'mandor', in Indonesian) in charge of coordinating daily laborers and responsible for the construction's progress & financial report. These tasks often had problems, such as bookkeeping or managing construction workers. This research aims to develop an Android application for bookkeeping construction projects as a solution for construction managers to manage personal and non-personal resources. The development of this application uses an HCD (Human Centered Design) approach, which consists of 5 steps: user requirements gathering, problem grouping, designing, developing, and testing. The application is tested using the Blackbox and UAT (User Acceptance Test) method, gaining a 91.03% approval response. The research successfully provides an Android-based application that fulfills the needs of construction managers to work efficiently in managing personal and non-personal resources of the construction project.